Food and Nutrition Strategies in National Development: Ninth Report of the Joint FAO/WHO Expert Committee on Nutrition - Joint FAO/WHO Expert Committee on Nutrition, Rome, 1974. (Rome: Food and Agriculture Organization of the United Nations and World Health Organization, 1976)
The Ninth Session of the Joint FAO/WHO Expert Committee on Nutrition met in Rome from 11 to 20 December 1974. The special topic for discussion was food and nutrition strategies in national development. The objectives of the meeting were: 1) to review the scope and objectives of a national food and nutrition policy; 2) to review methodological approaches in food and nutrition planning and provide guidance on a scientifically sound yet practical method, particularly for developing countries; 3) to recommend a workable mechanism for integrating nutrition into national development plans; and 4) to identify areas of training and research, particularly those calling for action by FAO and WHO for the improvement of the methodology of national food and nutrition policy formulation.
Includes bibliographical references.
ne 9/04/2018
Loans
Keywords: Nutrition Policy; Food Supply